ANALISIS NILAI TUKAR PETANI BUNGA KRISAN PADA ANGGOTA KELOMPOK TANI GEMAH RIPAH DI DUSUN CLAPAR DESA DUREN KECAMATAN BANDUNGAN KABUPATEN SEMARANG - Lana Khusnia Shifa; Kustopo Budiraharjo; Wiludjeng Roessali (SOCA: Jurnal Sosial Ekonomi Pertanian, 2019)
Chrysanthemum flowers are a commodity that has the potential to be used as a source of income. Problems that often in chrysanthemum farming are the relatively small scale of farming, unstable price fluctuations and lack of knowledge of farmers on the calculation of production costs and income. Farmer welfare can be measured by farmer exchange rate. This study aims to analyze the NTP in 2017 with 2018 and to analyze the factors that influence the NTP of chrysanthemum flowers. This research was conducted in october 2018 at the gemah ripah farmer group. The research method used is the census method. The number of respondents is 30 people who are members of the gemah ripah farmer group. The method of analisys uses quantitative methods by calculating chrysanthemum NTP, paired sample T-test and multiple linier regression test. The results of the analysis show that NTP in 2017 is 175% up to 179% in 2018, this means that farmers are in a prosperous condition. The paired sample T-test results showed a significant difference between NTP in 2017 and 2018 with a significance value of 0,017 < 0,05. Variable area of land, production costs, receipt of chrysanthemum farming, household expenses and family members significantly influence the NTP of chrysanthemum.